INTERNET DAN MUSIK: MEDIA SOSIAL SEBAGAI WAHANA PUBLIKASI THE UPSTAIRS DAN DEATH FLAMES - Sujud Puji Nur Rahmat; Lono Simatupang; Harsawibawa Albertus (Institut Seni Indonesia Yogyakarta, 2018)
Nowdays internet has become an important elemen in people life across the globe. Its impact has been seen in various scenes including music business and other artistic fields. Social media, running in support of internet, are now common in use by musicians or bands. Free of charge and global access of internet and social media provide an opportunity to disseminating the existence of a group of musicians. In this paper I would to show how social media has been utilized by a band to promote their group by themselves, focusing on myspace account of two bands, The Upstairs and death Flames. I divide this paper into introduction, an overview of www.myspace.com as well as a brief profile of the two bands, and a discussion on their account, kinds of responses and communication that established based on the accounts. Keywords: internet, musicians, band,and disseminating